Noninvasive ventilation as the first choice of ventilatory support in children - Lins, Aline Rafaele Barros da Silva (Rev Bras Ter Intensiva, 2019)
OBJECTIVE: To describe the use of noninvasive ventilation to prevent tracheal intubation in children in a pediatric intensive care unit and to analyze the factors related to respiratory failure. METHODS: A retrospective cohort study was performed from January 2016 to May 2018. The study population included children aged 1 to 14 years who were subjected to noninvasive ventilation as the first therapeutic choice for acute respiratory failure. Biological, clinical and managerial data were analyzed by applying a model with the variables that obtained significance ≤ 0.20 in a bivariate analysis. Logistic regression was performed using the ENTER method. The level of significance was set at 5%. RESULTS: The children had a mean age of 68.7 ± 42.3 months, 96.6% had respiratory disease as a primary diagnosis, and 15.8% had comorbidities. Of the 209 patients, noninvasive ventilation was the first option for ventilatory support in 86.6% of the patients, and the fraction of inspired oxygen was ≥ 0.40 in 47% of the cases. The lethality rate was 1.4%. The data for the use of noninvasive ventilation showed a high success rate of 95.3% (84.32 - 106). The Pediatric Risk of Mortality (PRISM) score and the length of stay in the intensive care unit were the significant clinical variables for the success or failure of noninvasive ventilation. CONCLUSION: A high rate of effectiveness was found for the use of noninvasive ventilation for acute episodes of respiratory failure. A higher PRISM score on admission, comorbidities associated with respiratory symptoms and oxygen use ≥ 40% were independent factors related to noninvasive ventilation failure.